Rancang Bangun Aplikasi Game Futsal antar Tim berbasis Android menggunakan Algoritma String Matching - Marisa (LPPM STT Terpadu Nurul Fikri, 2020)
Nowadays the growth of technology more and more people use smartphone technology, more information and increase knowledge or carry out various online activities. In this study, the authors make a futsal game application looking for opponents between teams, this application will be used by indoor soccer teams or futsal sports fans. the team that wants to play can search for the teams registered in this application easily. Team features, team photos, team criteria and detailed information about the team liaison at the same time that can be searched according to team criteria. With this application, the futsal team can easily find opponents who will be invited to compete, to support the creation of this system the author uses the String Matching algorithm or word matching is an important subject in relation to text-processing, simply the simple concept of string matching can be translated as a way to find the same string in a text (document) or database.